Identitas matematis: Studi kasus pada siswa dyscalculia - Astuti, Ririn Novia; Subanji, Subanji; Rahardi, Rustanto (UNIVERSITAS NEGERI MALANG, 2022)
This study aims to describe mathematical identity of dyscalculia student’s. The research method used descriptive qualitative with study case strategy. The research was conducted in SMP Negeri 18 Kota Malang. The subject of this study was a dyscalculia student who was 13 years old. Dyscalculia students were chosen as research subjects because these students were more open than other dyscalculia students. The results of the analysis are (1) mathematical identity regarding self-perception of mathematical competence that not all students who experience dyscalculia have a negative perception of mathematical competence because student worksheets can still state that they enjoy, like and do not feel bored when learning mathematics in special inclusive classes (2) mathematical identity regarding self-perception of mathematical participation are not yet independent in doing math assignments, teachers or parents always helping when studying, lack of motivation from friends, always re-recording material, and dare to ask others so they don't make mistakes and (3) Mathematical identity regarding self-perception of commitment and ambition to succeed in mathematics, are not afraid of failure, less persistent in completing exams, difficult to take the initiative to find new things, not afraid to ask questions and ask for help and less work hard in exams.